Donor Hypernatremia Influences Outcomes Following Pediatric Liver Transplantation - Kaseje, Neema; Lüthold, Samuel; Mentha, Gilles; Toso, Christian; Belli, Dominique; McLin, Valérie; Wildhaber, Barbara (European Journal of Pediatric Surgery, 2013)
Introduction With the rising demand for liver transplantations (LTs), and the shortage of organs, extended criteria including donor hypernatremia have been adopted to increase the donor pool. Currently, there is conflicting evidence on the effect of donor hypernatremia on outcomes following LT. Our aim was to investigate differences in outcome in patients receiving grafts from hypernatremic donors compared with patients receiving grafts from normonatremic donors in the pediatric population.Methods We retrospectively reviewed 94 pediatric patients with LTs from 1994 to 2011. We divided the patients into two groups: patients receiving organs from donors with sodium levels < 150 µmol/L, n = 67 (group 1), and patients receiving organs from donors with sodium levels ≥ 150 µmol/L, n = 27 (group 2). Using proportions and means, we analyzed patient age, sex, weight, model for end-stage liver disease (MELD) score, primary diagnosis, emergency of procedure, intraoperative transfusion volume, cold ischemia time, donor age, graft type, and postoperative graft function. Rates of mortality, rejection, early biliary, infectious, and vascular complications were calculated.Results Mean age was 3.9 years in group 1 and 3.7 years in group 2 (p = 0.69). Mean weight and MELD scores were similar in the two study groups (16.0 vs. 15.9 and 21.2 vs. 22.0, respectively). There were no significant differences in mean cold ischemia times 6.4 versus 6.9 hours (p = 0.29), and mean intraoperative transfusion volumes 1,068.5 mL versus 1,068.8 mL (p = 0.89). There were no statistically significant differences in mortality rates (7.3 vs. 11.1%, p = 0.68). Prothrombin time (PT) at day 10 post-LT was significantly lower in group 2 (79 vs. 64, p = 0.017), and there was a higher relative risk (RR) for early thrombotic vascular complications in group 2 (RR = 2.48); however, this was not significant (p = 0.26). No significant differences in RR for rejection (0.97, p = 0.86), viral infections (1.24, p = 0.31), bacterial infections (0.86, p = 0.62), or early biliary complications (1.03, p = 1.00) were observed.Conclusion In pediatric LT patients receiving grafts from hypernatremic donors, there are no significant increases in rates of mortality, rejection, early biliary, and infectious complications. However, there is a statistically significant lower PT at postoperative day 10 following transplantation, and a more than double RR for early thrombotic vascular complications although this was not statistically significant.
Keywords: hypernatremia; pediatric liver transplantation; outcomes